Transmission electron microscopy and spectroscopy of carbon-based nanomaterials - Rezvani, Ehsan (Trinity College (Dublin, Ireland). School of Chemistry, 2016)
Carbon-based nanomaterials, such as graphene, Carbon Nanotubes and fullerenes, have attracted a great deal of interest from the materials research community; especially in electronic and sensing applications. Despite all these outstanding properties, these materials pose significant challenges to the established characterisation techniques. Transmission electron microscopy (TEM) is considered as a powerful tool to tackle this challenge due to its capability to achieve images of atomic-scale resolution. Nonetheless, a key requirement for efficient application of TEM, is sample quality. To meet this need, in the first part of this work, modification of the CVD growth of graphene via catalyst optimisation was investigated and is reported in a dedicated chapter. We show that chromium can be used to successfully obtain entirely monolayer graphene films. The second part of this study, comprises HRTEM/EELS investigation of plasma-functionalised graphene; where we propose application of these two methods as a tool to monitor the quality of plasma-treated graphene sheets. We then move on to explore the bonding properties of isotope-enriched graphene studied by Aberration-Corrected TEM. The results show that the bonds in isotope graphene are stronger and remarkably longer comparing to those of “normal” graphene.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin